The Financial Support for Long-Term Elderly Care and Household Savings Behaviour - Asako Ohinata; Matteo Picchio (Institute for the Study of Labor (IZA), 2015)
We analyse how the financial support for long-term elderly care affects the level of household savings. Using a difference-in-differences estimator, we investigate the 2002 Scottish reform, which introduced free formal personal care for all the elderly aged 65 and above residing in Scotland. Our semiparametric estimation technique allows the policy effects to be flexibly estimated across age groups. We find that the Scottish policy reduced the average household saving by about 7,200. Moreover, the estimated effects are heterogeneous across age groups of the head of household: these effects are particularly strong among those aged between 40 and 60. The largest effect is observed at age 49 with the reduction in the average household saving by 12,764.
Keywords: C21; D14; I18; J14; 330; long-term elderly care; ageing; means tested financial support; saving; wealth; difference-in-differences